PEMILIHAN JENIS PENANGKAL PETIR UNTUK MENGAMANKAN AREA GEDUNG BESERTA PERALATAN PADA PERUMAHAN NUSA DUA HIGHLAND - Biantoro, Kharis; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUM, 2020)
The selection of lightning rods in the Nusa Dua Highland housing estate aims to secure the housing area from lightning strikes, because the housing has not been protected by lightning rods and earthing system components which are very difficult because they have rocky soil types. The average number of lightning strikes per year with a density value of 31 per km2 and population density, land use for houses and buildings have a very high level of vulnerability, so lightning rods are needed to secure the Nusa Dua Highland residential area. Lightning rods to be used are conventional lightning rods or Evo Franklin (E.F). The selection of the type of lightning rod is done by analyzing technical and economical. The results achieved in this study are the type of lightning rod suitable for housing Nusa Dua Highland is the E.F lightning rod with an earthing system. Because from technical analysis, 1 E.F lightning rod is able to protect the entire residential area with 37,994 m2 of protection area from the 22,444 m2 housing area, while 1 conventional lightning rod is only able to protect 1 house from a total of 147 housing units. In terms of economical cost of installing E.F lightning rods is much cheaper at a cost of Rp. 104,450,000. Conventional lightning rods cost Rp. 14,390,000 for 1 housing unit and to protect the entire housing using conventional lightning rods needed 147 lightning rods at a cost of Rp. 2,115,390,000.